Evidence for adjustable bandwidth orientation channels - Taylor, Christopher P.; Bennett, Patrick J.; Sekuler, Allison B. (Frontiers in Psychology, 2014)
The standard model of early vision claims that orientation and spatial frequency are encoded with multiple, fixed-bandwidth, and approximately independent channels. The standard model was developed from observer data that used deterministic patterns such as Gabor patches and gratings used as stimuli, but detection data using noise as a stimulus suggests that the visual system may use adjustable, rather than fixed-bandwidth channels. In our previous work, we used classification images as a key piece of evidence against the adjustable channels hypothesis for spatial frequency. Here we tested the adjustable channels hypothesis for orientation with two-dimensional filtered noise that varied in orientation bandwidth presented in white noise. Unlike spatial frequency, our data were consistent with the predictions of an adjustable channel model; we found quarter-root law thresholds consistent with optimal summation, relatively high and constant absolute efficiency, and classification images that show an adjustment in channel bandwidth. Thus, for orientation summation, both detection thresholds and classification image results support the adjustable channels hypothesis. Classification images also reveal hallmarks of inhibition or suppression from uninformative spatial frequencies and/or orientations. This work highlights the limitations of the standard model of summation for orientation. The standard model of orientation summation and tuning was chiefly developed with narrow-band stimuli that were not presented in noise, stimuli that are arguably less naturalistic than than the variable bandwidth stimuli presented in noise used in our experiments. Finally, the disagreement between the results from our experiments on spatial frequency summation with the data presented in this paper suggests that orientation may be encoded differently, particularly with mechanisms with greater flexibility than spatial frequency channels.